EFFECT OF RUTIN AGAINST HIGH-FAT DIET AND ALCOHOL-INDUCED ALTERATIONS IN HEMATOLOGICAL VARIABLES OF RATS - Kumar Chandra, Hemeshwer; Mishra, Gita; Sahu, Nisha; Kumar Nirala, Satendra; Bhadauria, Monika (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: Alcohol abuse leads to several diseases and millions of death worldwide. High-fat diet (HFD) is major contributor of non-alcoholic liver diseases and obesity. Combined consumption of HFD and alcohol has deleterious effect on blood cells. This study was carried out to evaluate the protective effect of rutin against combined consumption of HFD and alcohol-induced hematological alterations. Methods: HFD 30% and ethanol 10% were administered for 4 weeks for induction of toxicity. Rutin (10, 20, and 40 mg/kg) and 50 mg/kg dose of silymarin were administered along with HFD and alcohol for 4 weeks. Results: Combined consumption of HFD and alcohol increased mean corpuscular volume, total leukocytes count, eosinophil and monocyte, and decreased hematocrit and platelets. Administration of rutin improved hematological variables altered by HFD and alcohol consumption. Conclusion: The present study concluded that administration of rutin may alleviate HFD and alcohol-induced hematological alterations by scavenging free radicals generation.